PENGARUH KEJELASAN SASARAN ANGGARAN, PARTISIPASI MASYARAKAT DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA PADA KANTOR DESA SE-KECAMATAN MARGA KABUPATEN TABANAN - Ni Komang Sintia Dwipayani; Putu Nuniek Hutnaleontina (UNHI Press, 2022)
This study aims to determine and empirically test the clarity of budget targets, community participation, and government internal control systems1 on village fund management accountability.1 The factors that affect village fund management accountability are clarity of budget targets, community participation, and government internal control systems. The sample used in this study were 16 villages located in Marga District, Tabanan Regency with 80 respondents. The sampling method in this study used purposive sampling, data was collected using a questionnaire. The data analysis technique used multiple linear regression analysis. Based on the results of this study, it is stated that the clarity of budget targets and the government's internal control system1 has a positive effect 1 on 1 accountability 1 management 1 village funds, 1 while 1 community participation has no effect 1 on 3 accountability 2 management 2 funds 3 villages.